OPTIMALISASI CITRA MSCT TRAKTUS URINARIUS MENGGUNAKAN TRACKING DENGAN VARIASI SLICE THICKNESS DAN WINDOW SETTING - Nanang Sulaksono; Suryono Suryono; Jeffri Ardiyanto (Poltekkes Kemenkes Semarang, 2016)
Kidney disease is a clinical situation which is indicated by the decreasing of kidney functions and MSCT is one of the modalities to diagnose that function. The research was aimed to prove that the use of Tracking with variation in Slice Thickness and window setting was able to produce an optimal image after contrast value analysis was conducted. The method was the experimental research using research planning Pretest-Posttest Control Design. The sampling was chosen consecutively. There were 3 Radiolog and 21 patients on the examination of MSCT abdomen without positive contrast media in Salatiga Public Hospital. The research was conducted from May to July 2015. Research Results, the intervention validity experiment before and after using Tracking with Paired T-Test statistic experiment showed p value 0,000. There were some significant differences. Through Mann Whitney experiment, it was found that there was different result of p value 0,000 (p less than 0,05). There were significant differences in each group. It can be Concluded that The significant difference before and after using Tracking shows that Tracking can be used as an alternative for MSCT uroraphy examination.